2020
DOI: 10.14202/vetworld.2020.1495-1509
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of brucellosis in sheep and goats in the Arabian Gulf region

Abstract: Background and Aim: Brucellosis is a zoonosis that occurs worldwide. There were more efforts to control brucellosis in all countries. This study was performed to determine the seroprevalence of brucellosis in sheep and goats in some areas in the Arabian Gulf. Materials and Methods: The study analyzed 8500 sera from non-vaccinated sheep and goats. Animals included 6441 sheep (3420 from farms and 3021 from quarantine) and 2059 goats (1580 from farms and 479 from quarantine). Sera were tested using the Rose Beng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
2
21
2
Order By: Relevance
“…However, they recommended that vigilance be maintained to maintain its status of being free from this zoonosis in sheep and goats. Our results are also higher than the rate of 0.48% obtained by Ebid et al [37]. Our results are also above 3.2% obtained in China [38].…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…However, they recommended that vigilance be maintained to maintain its status of being free from this zoonosis in sheep and goats. Our results are also higher than the rate of 0.48% obtained by Ebid et al [37]. Our results are also above 3.2% obtained in China [38].…”
Section: Discussioncontrasting
confidence: 69%
“…Indeed, it is more easily transmitted to humans than bovine brucellosis [22,23]. This zoonotic transmission generally occurs through assisting with births and abortions, handling newborns without gloves, and consuming raw unpasteurized milk [30,35,37].…”
Section: Discussionmentioning
confidence: 99%
“…Considering sheep, the findings of the current study yield support the results of a study conducted by Samaha (2008) who found that seroprevalence among sheep was 0.00%. In the same vein, Bekele et al (2011) and Ebid and Salib (2020) respectively reported similar estimates of 1.2% and 0.48%, which were lower than the estimated rates of 20% and 15% respectively reported in the studies conducted by Abdel-Razik et al (2007) and Hegazy et al (2009). Similar to the obtained results of the current study concerning goats, (Samaha, 2008) estimated seroprevalence rates as 0.00%, which was almost near to the reported rates of 1.3% and 1.9% mentioned by Tekleye et al (1989) and Megersa et al (2011), respectively.…”
Section: Discussionmentioning
confidence: 88%
“…Recent data from sheep in Wyoming, USA, indicate 0.53% seropositivity in flocks and 22.5% among individual sheep [27]. Elsewhere, 0.71% seropositivity was noted in sheep in the Arabian Gulf [30] and 0% among 213 sheep tested in the Borana pastoral area in Ethiopia [31]. However, no new data has been obtained from other regions of the world, including Europe.…”
Section: Brief Description Of the State Of Knowledgementioning
confidence: 99%